Knowledge Graph Visualization Interface for Digital Heritage Collections: Design Issues and Recommendations - Khoo, Christopher S.G.; Tan, Eleanor A.L.; Ng, Siam-Gek; Chan, Chwee-Fong; Stanley-Baker, Michael; Cheng, Wei-Ning (Information Technology and Libraries, 2024)
Digital heritage portal interfaces are generally similar to digital library and search engine interfaces in displaying search results as a list of brief metadata records. The knowledge organization and search result display of these systems are item-centric, with little support for identifying relationships between items. This paper proposes a knowledge graph system and visualization interface as a promising solution for digital heritage systems to support users in browsing related items, understanding the relationships between items, and synthesizing a narrative on an issue. The paper discusses design issues for the knowledge graph, graph database, and graph visualization, and offers recommendations based on the authors’ experience in developing three knowledge graph systems for archive and digital humanities resources: the Zubir Said personal archive collection at the Nanyang Academy of Fine Arts, Singapore; Singapore Pioneers social network; and Polyglot Medicine knowledge graph of Asian traditional and herbal medicine. Lessons learned from a small user study are incorporated in the discussion.